The Effect Of Corruption, Democracy And Foreign Debt On Economic Growth In Asian Pacific Countries - Rommy Fernando Putra; Dewi Zaini Putri (Gorontalo State University, 2021)
Economic growth can be defined as a process of changing the economic conditions of a country on an ongoing basis towards a better condition during a certain period. This study aims to examine the effect of corruption, democracy and external debt on economic growth in 7 countries Asia Pasific. This is because of The Asia Pacific became known around the 1980s when financial market, international trade and political condition have increased. The data used is panel data during the period 2014-2018, and collected by data documentation and library obtained from World Bank, International Transparency and Freedom In The World. Using the panel data regression, the estimation results are (1) Corruption has a positive and significant effect on economic growth in 7 Asia Pacific countries, with a regression coefficient value of -0.2753, (2) Democracy has a positive and significant effect on economic growth in 7 Asia Pacific countries with a regression coefficient value of 0.0586, (3) External debt has a significant positive effect on economic growth in 7 countries Asia Pacific region with a regression coefficient of 0.7604 (4) Corruption, Democracy and External Debt have a significant effect on economic growth in 7 countries in the Asia Pacific region, with a probability value (F-statistic) of 0.0008